Zoo animal training – implications for the human-animal relationship, control and motivation : case study training red panda (Ailurus fulgens) for husbandry procedures - Aspenström, Sarah (SLU/Dept. of Animal Environment and Health (until 231231), 2018)
Zoo animals are trained for a lot of different reasons including facilitating husbandry procedures, physical exercise and mental stimulation. Training has also been shown to reduce stereotypies in captive wild animals. Among other factors, two of the most important for zoo animal welfare are the Human-Animal Relationship (HAR) between animal and zookeepers, and an environment that allows behavioural choices. These factors are important for the animal´s perceived level of control of its environment. This study is divided into two parts. First, it aims to investigate trainings implications for the HAR, control and motivation. Second, it also includes a case study of training Red Panda (Ailurus fulgens) for weighing and transporting.